Highly flexible and bendable carbon nanosheets as transparent conducting electrodes for organic solar cells - Son, Su-Young; Yun, Jin-Mun; Noh, Yong-Jin; Lee, Sungho; Jo, Hae-Na; Na, Seok-In; Joh, Han-Ik (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
We synthesized highly flexible carbon nanosheets (CNSs) as transparent conducting electrodes (TCEs) suitable for flexible organic solar cells (OSCs). The flexible electrodes were obtained by transferring CNSs, which were synthesized on recyclable silicon wafers using a catalyst-free process, onto a polyethylene terephthalate substrate. The TCEs exhibited a sheet resistance of similar to 2 .5 kohm/sq. and a transmittance of 61% even after 200 bending cycles, leading to a high power conversion efficiency of approximately similar to 1.33%, which is very high compared to that of flexible OSCs composed of pristine graphene generated by chemical vapor deposition or chemical exfoliation methods. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: NANOWIRE ELECTRODES; GRAPHENE; DEPOSITION; EFFICIENT; DEVICES; FILMS